Relationships of Syria and Turkey in the Sphere of Water Resources - Roda Hourie (Проблемы постсоветского пространства, 2019)
This article focuses on the relationship of Syria and Turkey in the field of water resources. The author studies the chronology of the development of relations between Syria andTurkey on the stated issues, historical background and causes of conflict situations. The positionsof Syria, Turkey and Iraq on the current controversial situations related to the use of shared water resources are analyzed. The author focuses on the vital importance of water resources for theeconomy and national security of Syria. The role of regional integration associations in resolvingconflict situations on the stated issues is revealed.